Formation of Orthogonal Components of Input Currents in Microprocessor Protections of Electrical Equipment - F. A. Romaniuk; Yu. V. Rumiantsev; V. Yu. Rumiantsev; I. V. Novash (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The methods used in the microprocessor protection of electrical equipment for forming orthogonal components of input currents ensure their reliable isolation after changing the mode followed by one or more periods of the fundamental frequency. This is due to the inertia of the functional elements, in particular, digital frequency filters, as well as the saturation of the steel magnetic cores of current transformers. To increase the speed of the selection of orthogonal components of the input currents, it is proposed to form them as equivalent ones in terms of the cosine and sine components obtained using digital Fourier filters by multiplying by the resulting coefficient. The method that has been developed for determining the specified coefficient provides compensation for the delay caused by the inertia of digital filters, as well as the saturation of the steel of magnetic cores of current transformers. The proposed method of forming orthogonal components is highly effective in the modes of strong saturation of the magnetic core with a complex input action in the presence of an aperiodic component with a large damping time constant. The evaluation of the efficiency of the proposed method was performed using a complex digital model implemented in the dynamic modeling environment MatLab-Simulink. As a result of the performed studies, it was found that in the absence of saturation of the magnetic core of current transformers, as well as in the presence of a small and medium degree of saturation, the proposed method for forming equivalent orthogonal components of input currents has dynamic properties close to the ones of those that had been previously proposed. With a strong saturation of the magnetic core of current transformers, the speed of obtaining reliable values of these components is increased by 1.5–2 times.